2017
DOI: 10.3390/ijms18040717
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles as Therapeutic Agents in Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a heterogeneous autoimmune disease that affects multiple organs. Currently, therapeutic molecules present adverse side effects and are only effective in some SLE patient subgroups. Extracellular vesicles (EV), including exosomes, microvesicles and apoptotic bodies, are released by most cell types, carry nucleic acids, proteins and lipids and play a crucial role in cell-to-cell communication. EVs can stimulate or suppress the immune responses depending on the context. In SL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 89 publications
1
34
0
Order By: Relevance
“…48 On the other hand, ameliorative effect of treatment with exosomes derived from MSCs in different autoimmune experimental models including osteoarthritis, systemic lupus erythematosus, rheumatoid arthritis in concordance with the results of the current study may be indicative of the importance of different sources of exosomes and even the source of the MSCs, and the importance of dominant microenvironment. 49,50…”
Section: Discussionmentioning
confidence: 99%
“…48 On the other hand, ameliorative effect of treatment with exosomes derived from MSCs in different autoimmune experimental models including osteoarthritis, systemic lupus erythematosus, rheumatoid arthritis in concordance with the results of the current study may be indicative of the importance of different sources of exosomes and even the source of the MSCs, and the importance of dominant microenvironment. 49,50…”
Section: Discussionmentioning
confidence: 99%
“…SLE is an immune complex disease where disease symptoms arise due to the reduced clearance of immune complexes, which leads to complement-mediated inflammation. EVs also associate with immunoglobulins and enhance the formation of such pathological immune complexes in SLE [ 54 ]. A recent study showed that distinct subpopulations of EVs harboring immunoglobulins were associated with distinct clinical characteristics of SLE and may therefore serve as biomarkers in future [ 55 ].…”
Section: Evs and The Blood Plasmamentioning
confidence: 99%
“…Exosome and microvesicles are emerging as novel therapeutic targets in treatment of disease as they have been shown to contribute to inflammatory processes ( Foers et al, 2017 ) and the progression of numerous pathologies including autoimmune diseases ( Antwi-Baffour et al, 2010 ; Withrow et al, 2016 ; Perez-Hernandez et al, 2017 ), cancers ( Luga et al, 2012 ; Jorfi et al, 2015 ; Kholia et al, 2015 ; Stratton et al, 2015a ; Sung et al, 2015 ; Tkach and Théry, 2016 ; Moore et al, 2017 ; Sung and Weaver, 2017 ) and neurodegenerative diseases ( Colombo et al, 2012 ; Gupta and Pulliam, 2014 ; Porro et al, 2015 ; Basso and Bonetto, 2016 ). In cancer patients, elevated EMV levels have for example been demonstrated in the blood ( Ginestra et al, 1998 ; Kim et al, 2003 ; Zwicker et al, 2009 ) and EMVs can also aid tumor spread and survival as they transport various micro RNAs, pathological growth factor receptors and soluble proteins ( Muralidharan-Chari et al, 2010 ; Inal et al, 2012 ; Hoshino et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%